Pharmacological modulation of suppressor cell activity in mice with disseminated histoplasmosis. - Deepe, G S (1983)
Indomethacin and cyclophosphamide (CY) were used in an attempt to modify the suppressive effects of spleen cell populations from mice with disseminated histoplasmosis at 1 week of infection. In vitro addition of indomethacin did not alter the depressed plaque-forming cell response to sheep erythrocytes of normal spleen cells cocultured with unfractionated or nylon wool-fractionated spleen cells from infected mice. Likewise, indomethacin given intraperitoneally did not enhance the subnormal in vivo plaque-forming cell response of spleen cells from infected mice. Conversely, 20 mg of CY per kg given intraperitoneally 2 days before or 6 h after the inoculation with Histoplasma capsulatum partially reversed the suppression effected by splenic T cells (nylon wool passed) in vitro, whereas 50 mg of CY per kg given intraperitoneally 6 h after the injection of H. capsulatum ablated suppressor T cell activity in vitro; neither dosage of CY altered the suppression mediated by unseparated or nylon wool-adherent spleen cells. Furthermore, the administration of 50 mg of CY per kg failed to improve the depressed footpad responses of mice infected for 1 week to sheep erythrocytes in sheep erythrocyte-sensitized mice or to histoplasmin. These findings indicate that in experimental disseminated histoplasmosis, suppression effected by splenic T cells can be alleviated by CY; however, there is a persistent immunosuppressor mechanism(s) that cannot be counteracted by either indomethacin or CY.